An Anatomical Study of Median Nerve Branches for Distal Nerve Transfer in Isolated Anterior Interosseous Nerve Syndrome - Krit Utrapat, MD; Nuttapat Khusritheppratan, MD; Parunyu Vilai, MD; Vichununt Kerdput, PhD; Wisuit Pradidarcheep, PhD (Journal of Hand Surgery Global Online)
Purpose: Isolated anterior interosseous nerve (AIN) syndrome is a forearm compression neuropathy. A viable treatment for the syndrome is distal nerve transfer. However, the option of a donor nerve branch from the median nerve remains debated. This study aimed to identify the most suitable median nerve branch for distal nerve transfer in AIN syndrome patients by evaluating nerve diameter, fascicle and axon count, and distance between donor and recipient nerves. Methods: Twenty cadaveric arms were dissected to examine the AIN as the recipient nerve. Candidate donor nerves included branches to the palmaris longus (PL), flexor carpi radialis (FCR), and first and second branches of the flexor digitorum superficialis (FDS1 and FDS2). Each nerve length and the distance between donor and recipient nerves were measured. Histochemical staining was used to measure cross-sectional diameter and axon count. Results: All donor nerves had sufficient length for transfer, with FCR providing the greatest length (32.8 mm) and causing the least postoperative tension. Among the studied nerves, AIN had the largest diameter (2.3 ± 0.4 mm), followed by FCR (2.1 ± 0.3 mm), PL (2.0 ± 0.4 mm), FDS2 (1.6 ± 0.6 mm), and FDS1 (1.5 ± 0.3 mm). The AIN also had the highest average axon count (2747 ± 710), compared with FDS2 (888 ± 458), FCR (869 ± 366), PL (678 ± 277), and FDS1 (426 ± 192). Conclusions: The FCR branch transfer may not be the definitive best option for AIN palsy; however, it remains a highly viable and effective choice for reinnervation, providing a good alternative in cases where other donor nerves present anatomical or functional limitations Clinical relevance: This study provides anatomical and histological insights into the optimal median nerve branches for AIN transfer.